2004
DOI: 10.1111/j.0021-8790.2004.00822.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary self‐selection behaviour by the adults of the aphidophagous ladybeetle Harmonia axyridis (Coleoptera: Coccinellidae)

Abstract: Summary 1.Harmonia axyridis is a generalist predator with a high range of accepted prey. Prey differ in nutritive contents, energetic values and cost associated with their capture and ingestion. As a result of selection pressures, animals will tend to hunt for their prey efficiently. In this paper we evaluated the suitability of Myzus persicae and Aphis fabae to the adults of the aulica phenotype of H. axyridis , their feeding preferences and the impact of mixed diets on their fitness. Feeding preference of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 45 publications
(83 reference statements)
6
72
1
1
Order By: Relevance
“…While, as previously stated, H. axyridis showed high fecundity, other studies demonstrated similar or lower fecundity than indigenous species (Bazzochi et al 2004;Lanzoni et al 2004;Michaud and Olsen 2004;Soares et al 2004). For example, in Italy, the mean fecundity of H. axyridis (783.8 eggs per female) was only slightly higher than an indigenous species, A. bipunctata (720.2 eggs per female) (Bazzochi et al 2004).…”
Section: Harmonia Axyridis: a Super Invader?supporting
confidence: 58%
See 1 more Smart Citation
“…While, as previously stated, H. axyridis showed high fecundity, other studies demonstrated similar or lower fecundity than indigenous species (Bazzochi et al 2004;Lanzoni et al 2004;Michaud and Olsen 2004;Soares et al 2004). For example, in Italy, the mean fecundity of H. axyridis (783.8 eggs per female) was only slightly higher than an indigenous species, A. bipunctata (720.2 eggs per female) (Bazzochi et al 2004).…”
Section: Harmonia Axyridis: a Super Invader?supporting
confidence: 58%
“…Lower fecundity of H. axyridis (560.5 eggs per female) compared to H. variegata (841.7 eggs per female) was observed in laboratory by Lanzoni et al (2004). Soares et al (2004) demonstrated an even lower fecundity than these experiments suggest, with a mean fecundity of 314 eggs per female for the aulica phenotype of H. axyridis in laboratory. Experiments of Michaud and Olsen (2004) on psyllids demonstrated similar fecundity of H. axyridis (242.8 eggs per female) to O. v-nigrum (224.5 eggs per female).…”
Section: Harmonia Axyridis: a Super Invader?mentioning
confidence: 51%
“…Although provision of fruit flies alone sustained a high level of spider reproduction, provision of aphids alone resulted in greatly reduced reproduction (and consumption of prey). Soares et al (2004) recorded significantly higher fecundity and fertility of H. axyridis when females fed on a mixed diet of Aphis fabae Scopoli and M. persicae rather than on a diet of either aphid alone. Thus by serving together in a mixed diet that enhances predator reproduction, prey species may indirectly interact with each other in negative fashion.…”
Section: Reproductive Responsementioning
confidence: 88%
“…The generalist tendencies of these predators may arise from low food availability (e.g., O'Neil & Wiedenmann, 1987;Bilde & Toft, 1998;Beckman & Hurd, 2003;Wise, 2006). In addition, the predators may benefit from balancing their nutritional requirements through a mixed diet (e.g., Greenstone, 1979;Soares et al, 2004;Mayntz et al, 2005). Given the generalist tendencies of most predatory arthropods, it is generally thought that their impact on a particular prey species in a given habitat (e.g., an insect pest in a crop) will depend frequently on the local availability of alternate prey (with "prey" broadly including plant resources such as fruit and pollen in the case of omnivorous predators) (e.g., van Emden, 1965;Symondson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The presence or absence of extraguild prey influences the intensity of the interactions (Agarwala & Dixon, 1992;Rosenheim et al, 1995;Lucas et al, 1998;Hindayana et al, 2001;Meyhöfer, 2001). The black bean aphid, Aphis fabae Scop., was selected as the extra-guild prey because it is a moderately suitable prey for the larval development of the species studied or a common prey item in the habitats studied (Hodek & Honek, 1996;Stathas et al, 2001;Soares et al, 2004;Barbagallo & Ricci, 2006).…”
Section: Introductionmentioning
confidence: 99%